Explanation:
an equation is a function, if it delivers for every possible input value x exactly one result value y.
b(x) = y = x² + 3
y - 3 = x²
x = sqrt(y -3)
our formally correct
y = sqrt(x - 3)
that is actually NOT a function, as a square root delivers for most x values 2 y values : a positive and a negative value.
d(x) = -9
that means for every possible value of x the result is -9.
reversing this means that the input value of -9 has infinitely many possible results
that is NOT a function.
m(x) = y = -7x
x = -y/7
or formally correct
y = -x/7
that is a normal function. every possible value of x leads to exactly one value of y.
p(x) = y = 1x¹ = x
y = x is its own inverse function.
and this is, of course, a function. every possible value of x leads to exactly one value of y.